A Multimodal Robotic Communication System for Students with Profound and Multiple Disabilities (The International Journal of Engineering & Information Technology (IJEIT), 2015)
Different researches claim that using a robot to play with students with profound and multiple disabilities might be a valuable tool to increase the learning curve of those students. Robots in schools and in other educational environments is a growing research field and it seems that it is time for technology to transform the education with people of special needs similarly to how technology affected mainstream education. The project focuses on using different switches plugged in a joybox to send signals to NAO Robot. Each switch caries a certain behavior. JoyBox contains eight numbered connectors and four direction connectors to move the robot. The paper implements client server communication to connect to the robot and be able to send signals to the robot via the switches connected to the JoyBox. Using the switch enables the users to communicate to NAO independently. This gauntness a deep level of engagement with the robot, since the robot moves based on the singles received from the switches. The paper describes the setup of the client server communication, and the robot knows which behaviour to implement next. This study implements a case study evaluated by only four researchers and staff from Oakfield school to evaluate the software .This study hopes to be able to assess the needs of school staff to improve communicational methods for students with profound and multiple disabilities.